2015
DOI: 10.1159/000377653
|View full text |Cite
|
Sign up to set email alerts
|

SOX3 Overdosage Permits Normal Sex Development in Females with Random X Inactivation

Abstract: Submicroscopic duplications involving SOX3 and/or its flanking regions have been identified in 46,XX individuals both with and without disorders of sex development, raising the question whether SOX3 overdosage is sufficient to induce testicular development in genetically female individuals. Here, we report a mother-daughter pair with female phenotypes and random X inactivation. The individuals carry complex X chromosomal rearrangements leading to a copy number gain of genomic regions involving SOX3 and its ups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Although SOX3 does not seem to be required for normal testicular differentiation, its overexpression in the developing XX mouse gonad provokes testicular development, by synergizing with SF1 to upregulate SOX9 expression . It should, however, be noticed that a SOX3 duplication may not be sufficient to induce testicular differentiation when the regulatory sequences are lacking in the duplicated DNA fragment …”
mentioning
confidence: 98%
“…Although SOX3 does not seem to be required for normal testicular differentiation, its overexpression in the developing XX mouse gonad provokes testicular development, by synergizing with SF1 to upregulate SOX9 expression . It should, however, be noticed that a SOX3 duplication may not be sufficient to induce testicular differentiation when the regulatory sequences are lacking in the duplicated DNA fragment …”
mentioning
confidence: 98%
“…Most cases are maternally inherited. However, the mothers usually exhibit a normal phenotype, which may be due to skewed inactivation of the affected X chromosome (Arya et al, 2019; Hol et al, 2000); low penetrance of DSD caused by SOX3 overdosage has also been suggested (Igarashi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In XX mice lacking the SRY gene, it was found that the expression of the SOX3 gene with the acquired function was related to partial differentiation of testis. Overexpression of SOX3, synergistically expression with SF1, upregulated SOX9 stimulated gonad development into testis in XX mice [9,40]. SRY gene was derived from a new mutation in the regulatory region of the SOX3 gene and expressed in the early gonad.…”
Section: Discussionmentioning
confidence: 99%